Parallel imports under a manufacturer rebate and a price freeze: Evidence from Germany - Laura Birg (Health Economics, 2022)
I study the effect of a change in the mandatory manufacturer rebate and a price freeze on wholesale prices for pharmaceuticals on competition by parallel imports. First, I analyze the effect of a manufacturer rebate on competition by parallel imports in a two-country model. Second, I exploit a policy reform in Germany in 2010 that increased the manufacturer rebate by 10 percentage points. Using a data set with prescription drugs with competition from parallel imports, I estimate the effect of the change in the manufacturer rebate on competition by parallel imports. The model predicts that an increase in the manufacturer rebate increases the market share of parallel imports. The rebate decreases the manufacturer's revenues from domestic distribution. In response, the manufacturer lowers the wholesale price for a foreign distributor, resulting in a competitive advantage for and an increase in the market share of parallel imports. The estimation shows that the increase in the manufacturer rebate by 10 percentage points has increased the market share of parallel imports by approximately 18%–35% and has increased the number of importers by up to 17%.
Keywords: 330; manufacturer rebate; parallel imports; pharmaceuticals; regulation